Interactive Response Systems (IRS) in online English classes: Voices of foreign university teachers in Thailand - Kiki Juli Anggoro; Nurmala Nurmala (Universitas Syiah Kuala, 2024)
Technological advances have introduced English instructors to various ways of delivering successful online classes. Using an Interactive Response System (IRS) as a supporting tool is one of them. This qualitative study investigates the perceptions of foreign English language teachers in Thai universities regarding the use of IRS in online classes. The study involved 10 non-native English university teachers, 7 females and 3 males, aged 27 to 35, with 3 to 6 years of teaching experience in Thailand. They are affiliated with three different Thai universities. Data were gathered through multiple online interviews and observations via Zoom or Google Meet, tailored to each participants convenience. The data analysis was conducted using a robust content analysis approach. The findings of this study showed that educators integrated IRS tools to boost engagement, benefiting both students and instructors. Additionally, peer influence encouraged IRS adoption and enhanced teaching methods. IRS tools served various roles, ranging from assessment to promoting motivation and enhancing comprehension. The advantages of IRS tools included increased interactivity, competition, and engagement. They aided in monitoring student attentiveness and comprehension while fostering independent learning. Challenges such as unequal internet access, device limitations, technology literacy, fees, workload, and language barriers existed, along with concerns about potential cheating during IRS activities.